Shadows reel [large type] - Box, C. J. (Box, C. J. Joe Pickett novel., 2022)
"A day before the three Pickett girls come home for Thanksgiving, Joe is called out for a moose poaching incident that turns out to be something much more sinister: a local fishing guide has been brutally tortured and murdered. At the same time, Marybeth opens an unmarked package at the library where she works and finds a photo album that belonged to an infamous Nazi official. When a close neighbor is murdered, Joe and Marybeth face new questions: Who is after the book? And how will they solve its mystery before someone hurts them or their girls?''--